Perceiving through similitude - Emslie, Neville J. (Theology, 2025)
This article examines the intersection of poetry, theology and artistic creation as a means of perceiving deeper truths about the divine and human existence, focusing on the work of Charles Tomlinson. Arguing that poetic creation offers unique theological insights, the article challenges conventional religious frameworks by positioning the poet as a theological figure. Through the lens of similitude – a concept drawn from Augustine’s theology and exemplified in Milton’s work – the article explores how artists uncover hidden truths not through doctrinal certainty but through metaphor, analogy and emotional resonance. The article delves into Tomlinson’s ability to transform the ordinary into profound spiritual exploration, demonstrating how everyday experiences, such as the simple act of sunlight startling a cat, can reveal deeper theological and metaphysical insights. By engaging with similitude, Tomlinson’s poetry encourages readers to perceive the divine within the mundane, offering a vision of reality that is both sacred and transformative. Ultimately, the article argues that artistic perception serves as a form of theological inquiry.